Implementation of Restorative Justice to Resolve Child Criminal Cases in the South Sumatra Regional Police - Hendrik Paulus; Tegar Puji; Stanly Himawan Chandra; Alexandro Luis Davala; Dyson Franyus Linansera; Chandra Bayu Irawan; Mustafa Mustafa (Journal of Creative Power and Ambition (JCPA), 2026)
The Restorative Justice approach has attracted the attention of many parties, especially in cases involving children. Despite being popular, in-depth studies of Restorative Justice have not been carried out much. The research objective is to find out matters related to Restorative Justice by analyzing the legal basis, implementation and challenges to apply Restorative Justice to juvenile criminal cases. The research method used in this study is a normative juridical research method supported by empirical data. The locus of the research was the Directorate of General Criminal Investigation of the South Sumatra Police and the cases studied were juvenile crimes. There are three findings of this study, namely: (1). The legal basis for the Restorative Justice approach, (2) the magnitude of the influence of the implementation of resolving child crime cases through the restorative justice approach, (3) the obstacles investigators solve cases through the Restorative Justice approach. The solution offered is the implementation model of the Restorative Justice approach with a legal basic, competent human resources and community support.